Characterisation of Adsorbent Developed from Rice Husk: Effect of Surface Functional Group on Phenol Adsorption - Daffalla, Samah (2010)
In recent years, there has been a rapidly growing public concern about the widespread environmental pollution. Phenol and it derivatives are among the most common pollutants from various industrial effluents. They are considered as toxic to humans and aquatic life. The main objective of this study is to develop effective adsorbents from rice husk modified by thermal and chemical treatments for removal of phenol from industrial wastewater. The physical and surface properties of the developed adsorbents were characterized using FTIR, SEM and FSEM. It was found that the pretreatment of rice husk has increased the specific surface area and changed the functional groups (-OH, Si-OH, C-H, C=O, C=C, CH2, CH3, CO, Si-O-Si, C-C, Si-H, -O-CH3) onto the surface of adsorbent and these functional groups affects the sorption of phenol onto the surface of adsorbent. The effect of phenol on the adsorbents functional group was analyzed by comparing its properties before and after the experiment